Variants in the inflammatory IL6 and MPO genes modulate stroke susceptibility through main effects and gene-gene interactions - Manso, Helena (2011)
There is substantial evidence that inflammation within the central nervous system contributes to stroke risk and recovery. Inflammatory conditions increase stroke risk, and the inflammatory response is of major importance in recovery and healing processes after stroke. We investigated the role of inflammatory genes IL1B, IL6, MPO, and TNF in stroke susceptibility and recovery in a population sample of 672 patients and 530 controls, adjusting for demographic, clinical and lifestyle risk factors, and stroke severity parameters. We also considered the likely complexity of inflammatory mechanisms in stroke, by assessing the combined effects of multiple genes. Two interleukin 6 (IL6) and one myeloperoxidase (MPO) single-nucleotide polymorphisms were significantly associated with stroke risk (0.022<(corrected)P<0.042), highlighting gene variants of low to moderate effect in stroke risk. An epistatic interaction between the IL6 and MPO genes was also identified in association with stroke susceptibility (P=0.031 after 1,000 permutations). In a subset of 546 patients, one IL6 haplotype was associated with stroke outcome at 3 months ((corrected)P=0.024), an intriguing finding warranting further validation. Our findings support the association of the IL6 gene and present novel evidence for the involvement of MPO in stroke susceptibility, suggesting a modulation of stroke risk by main gene effects, clinical and lifestyle factors, and gene-gene interactions.